2014
DOI: 10.1371/journal.pone.0111402
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Physiological Responses of a Tropical Crop (Capsicum chinense Jacq.) at High Temperature

Abstract: Temperature is one of the main environmental factors involved in global warming and has been found to have a direct effect on plants. However, few studies have investigated the effect of higher temperature on tropical crops. We therefore performed an experiment with a tropical crop of Habanero pepper (Capsicum Chinense Jacq.). Three growth chambers were used, each with 30 Habanero pepper plants. Chambers were maintained at a diurnal maximum air temperature (DMT) of 30 (chamber 1), 35 (chamber 2) and 40°C (cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 24 publications
(28 reference statements)
0
15
2
5
Order By: Relevance
“…CO 2 assimilation rate (A N ), stomatal conductance (g s ) and transpiration (E) were measured using an infrared gas analyzer (IRGA; LICOR, LI-6400, Lincoln, Nebraska, USA). Water use efficiency (WUE) was calculated as A N /E (Garruña- Hernández et al, 2014). Measurements were performed in the same leaves used in chlorophyll fluorescence measurement.…”
Section: Chlorophyll Fluorescence and Gas Exchange Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 assimilation rate (A N ), stomatal conductance (g s ) and transpiration (E) were measured using an infrared gas analyzer (IRGA; LICOR, LI-6400, Lincoln, Nebraska, USA). Water use efficiency (WUE) was calculated as A N /E (Garruña- Hernández et al, 2014). Measurements were performed in the same leaves used in chlorophyll fluorescence measurement.…”
Section: Chlorophyll Fluorescence and Gas Exchange Analysesmentioning
confidence: 99%
“…In particular, Habanero pepper (Capsicum chinense Jacq.) grows in wide temperature range, and has therefore been used in studies of plant stress (Garruña-Hernández et al, 2014;Valle-Gough et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic factors such as low temperatures, high temperatures, salt stress, drought (Serrano et al, 2017), and waterlogging can limit pepper yield (Ou and Zou, 2012;Zhai et al, 2016). For instance, optimal temperatures for pepper photosynthesis range from 25 to 35°C, and temperatures outside this range can limit the yield; for example, C. chinense flower abortion increased 2-fold and fruit set decreased 3-fold when greenhouse temperatures were increased from 30 to 40°C (Garruna-Hernandez et al, 2014). Erickson and Markhart (2002) showed that Capcisum flower abortion after pollination was particularly sensitive to high temperatures (33°C).…”
mentioning
confidence: 99%
“…High temperatures affect many aspects of plant physiology and growth, which in turn may have a direct or indirect effect on crop yield (Erickson and Markhart 2001;Bhutia et al 2018). Many studies have shown the direct impact of increased or decreased temperature in the production of chili pepper (Garruna-Hernandez et al 2014;Bhutia et al 2018). Pepper that is grown under high temperature (33°C) shows reduced fruit set (Yanez-Lopez et al 2012;Bhutia et al 2018), and flower malformation when grown in temperatures below 18°C resulting in the formation of parthenocarpic fruits and reduced fruit set (Aloni et al 1999;Bhutia et al 2018).…”
Section: Introductionmentioning
confidence: 99%